2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346249
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wearable capacitive coupled and common electrode-free ECG monitoring system

Abstract: Nowadays, transfer of the health care from ambulance to patient's home needs higher demand on patient's mobility, comfort and acceptance of the system. Therefore, the goal of this study is to proof the concept of a system which is ultra-wearable, less constraining and more suitable for long term measurements than conventional ECG monitoring systems which use conductive electrolytic gels for low impedance electrical contact with skin. The developed system is based on isolated capacitive coupled electrodes witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This DRL electrode is usually placed at a distant site, far from the measurement electrodes and thus requires a long wired connection, which may not be convenient for wearable and long-term monitoring systems. Komensky et al [ 31 ] proposed an ECG monitoring system without the DRL circuit, where only two active capacitive sensors were embedded in an elastic chest band. In order to increase and stabilize the input impedance, two anti-parallel connected diodes were used for biasing that has advantages over resistors [ 30 ] of low thermal noise and fast recovery time.…”
Section: Wearable Health Monitoring Systemsmentioning
confidence: 99%
“…This DRL electrode is usually placed at a distant site, far from the measurement electrodes and thus requires a long wired connection, which may not be convenient for wearable and long-term monitoring systems. Komensky et al [ 31 ] proposed an ECG monitoring system without the DRL circuit, where only two active capacitive sensors were embedded in an elastic chest band. In order to increase and stabilize the input impedance, two anti-parallel connected diodes were used for biasing that has advantages over resistors [ 30 ] of low thermal noise and fast recovery time.…”
Section: Wearable Health Monitoring Systemsmentioning
confidence: 99%
“…caused by power supply grid). The authors conclude, as it is also found in [28] that the shielding is the most promising solution in order to improve the signal performance regarding noise.…”
Section: Conclussionsmentioning
confidence: 56%
“…This very first prototype shows promising results concerning the realization of a low cost, portable, contactless ECG measurement system solution for construction security purposes. Once the improvements are implemented in order to reduce the noise by shielding, as mentioned in [23], this system can be built to a 3 up to 6 lead ECG, in order to enable unobtrusive ECG measurements, according to Einthoven (I, II, III), and Goldberger (aVR, aVL, aVF) [24]. Also for this approach, appropriate Arduino shields are already available on the market [25], which would even decrease the developing cost, if only 1 lead is used, as it is done with the proposed system.…”
Section: Conclusion and Discussionmentioning
confidence: 99%